Recently Discovered Interstitial Cell Population of Telocytes: Distinguishing Facts from Fiction Regarding Their Role in the Pathogenesis of Diverse Diseases Called "Telocytopathies" - Varga, Ivan; Polák, Štefan; Kyselovič, Ján; Kachlík, David; Danišovič, Ľuboš; Klein, Martin (Medicina (Kaunas, Lithuania), 2019)
In recent years, the interstitial cells telocytes, formerly known as interstitial Cajal-like cells, have been described in almost all organs of the human body. Although telocytes were previously thought to be localized predominantly in the organs of the digestive system, as of 2018 they have also been described in the lymphoid tissue, skin, respiratory system, urinary system, meninges and the organs of the male and female genital tracts. Since the time of eminent German pathologist Rudolf Virchow, we have known that many pathological processes originate directly from cellular changes. Even though telocytes are not widely accepted by all scientists as an individual and morphologically and functionally distinct cell population, several articles regarding telocytes have already been published in such prestigious journals as Nature and Annals of the New York Academy of Sciences. The telocyte diversity extends beyond their morphology and functions, as they have a potential role in the etiopathogenesis of different diseases. The most commonly described telocyte-associated diseases (which may be best termed "telocytopathies" in the future) are summarized in this critical review. It is difficult to imagine that a single cell population could be involved in the pathogenesis of such a wide spectrum of pathological conditions as extragastrointestinal stromal tumors ("telocytomas"), liver fibrosis, preeclampsia during pregnancy, tubal infertility, heart failure and psoriasis. In any case, future functional studies of telocytes in vivo will help to understand the mechanism by which telocytes contribute to tissue homeostasis in health and disease.
Keywords: signální transdukce; Signal Transduction; Humans; fyziologická neovaskularizace; Receptor, Platelet-Derived Growth Factor beta; interstitial Cajal-like cells; Antigens, CD34; tissue regeneration; imunofenotypizace; Interstitial Cells of Cajal; Receptor, Platelet-Derived Growth Factor alpha; lidé; intersticiální Cajalovy buňky; růstový faktor odvozený z trombocytů - receptor alfa; růstový faktor odvozený z trombocytů - receptor beta; antigeny CD34; Telocytes; Immunophenotyping; homeostáza; telocyty; Homeostasis; regenerace; telocytoma; telocytes; telocytopathies; Neovascularization, Physiologic; Regeneration